2014
DOI: 10.1002/pbc.25104
|View full text |Cite
|
Sign up to set email alerts
|

Significant inconsistency among pediatric oncologists in the use of the neutropenic diet

Abstract: The implementation of the neutropenic diet by pediatric oncologists remains quite variable even among those at the same institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 10 publications
0
20
0
4
Order By: Relevance
“…The nutrient compositions of the diets were calculated based on the daily menus used for 6 days. For the neutropenic diet, two versions were examined: a strict diet that excluded raw and fresh foods (which is commonly used in most oncology centers) and a second version that included thick skinned fruits. Calculations were performed according to the reference values of the Brazilian food composition table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutrient compositions of the diets were calculated based on the daily menus used for 6 days. For the neutropenic diet, two versions were examined: a strict diet that excluded raw and fresh foods (which is commonly used in most oncology centers) and a second version that included thick skinned fruits. Calculations were performed according to the reference values of the Brazilian food composition table .…”
Section: Methodsmentioning
confidence: 99%
“…However, there is no scientific evidence to support its benefit, and this diet can lead to difficulties in compliance and oral intake . Moreover, the lack of knowledge regarding the neutropenic diet has led to a lack of uniformity in the dietary recommendations of centers . Therefore, the microbiological and nutritional contents of regular and neutropenic diets that are offered to pediatric patients were analyzed and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Differences were mainly with including fruits that could be peeled by hand (13), or further excluding black pepper, or raw or unpasteurized dairy products from the diet (14). Multiple surveys have looked at the frequency of ND use in various institutions and inconsistencies between and within centers (3)(4)(5)(6)17).…”
Section: The Effect Of a Neutropenic Dietmentioning
confidence: 99%
“…), uncooked meats, and vegetables are commonly consumed. Multiple surveys have shown that the use of ND varies not only across cancer centers but also between physicians working within the same institution (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Penjaga pesakit juga menyatakan nasihat pemakanan yang diberikan oleh ahli profesional kesihatan ada yang bercanggah sehingga mengelirukan mereka. Hasil kajian ini selari dengan laporan kajian lepas yang dikendalikan oleh Braun et al (2014) yang melibatkan seramai 557 orang pakar perunding onkologi kanak-kanak daripada 174 institut kanser kanak-kanak yang berdaftar dalam web Children's Oncology Group (COG). Kajian ini bertujuan untuk mengenalpasti amalan pelaksanaan diet neutropenik dan faktor yang mempengaruhi bagi tujuan penyeragaman pengurusan pemakanan dalam kalangan kanak-kanak kanser.…”
Section: Pengumpulan Dataunclassified